Development of needle-punched nonwovens made from waste milkweed and PET fibers - Tekbaş, Rana Nur; Karkın, Sevgi; Cengiz, Fehmi; Mula, Murat; Gürarslan, Alper (SAGE Publications, 2024)
Despite the widespread usage and affordability of petroleum-based products, there has been tremendous effort in prioritizing and utilizing biodegradable and environmentally friendly materials. Untraditional natural fibers play a critical role in sustainability studies; however, fibers such as kapok and milkweed are quite expensive compared to other plant-based natural fibers such as cotton and flax. Therefore, it is critical to utilize these untraditional fibers in the most efficient manner that is possible. In this study, short milkweed fiber leftovers collected from the milkweed yarn spinning process were utilized as a filler material inside the needle-punched nonwoven fabrics. For this purpose, short milkweed fibers were blended with hollow polyethylene terephthalate (PET) fibers to develop nonwovens. Three different sets of weight/g fabrics were prepared for both only PET containing and short milkweed/PET blended fibers. Thickness, weight, tensile and bursting strength, thermal comfort, air permeability, and water contact angle measurements were conducted for the samples. Consequently, the thermal resistance of short milkweed/PET blended fabrics with similar weight increased by up to 34% compared to only PET-containing fabrics. Results indicate that valuable short milkweed fibers are suitable for developing nonwoven fabrics with comparable physical properties and superior thermal insulation properties.
Keywords: chemical technology; milkweed; needle punching; sustainable nonwovens; textile bleaching, dyeing, printing, etc.; asclepia syriaca